The Press she could not whip : emergency in India as reported by the foreign press - Rao, Amiya, 1909-; Rao, B. G. (Popular Prakashan, 1977)
Selected newspaper reports criticising the proclamation of internal emergency in India, June 1975-March 1977, by Indira Gandhi, b. 1917, former Prime Minister of India, and the policies of the previous Indian administration.